2018
DOI: 10.1039/c8cp05014g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nano-pillared surfaces with an arrangement density gradient on droplet coalescence dynamics

Abstract: The ability to predict and control the coalescence of droplets is of great importance for both industrial and technological applications, including 3D printing, micro-cladding, and self-assembly. Here, a textured surface decorated with nano-pillared arrays was designed and its arrangement density (f) was found to significantly affect the coalescence dynamics of droplets through changing their wettability. A large arrangement density f of the nano-pillared arrays would induce a Cassie wetting state for droplets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…The use of pillared structure on the modified surface can not only tune the wettability of liquids but also significantly affect the coalescence dynamics. More recently, the effect of arrangement density ( f ) of nano‐pillared structures on the coalescence dynamics has been reported . As shown in Figure a, the nano‐pillared surface is built by the vertical VCNTs, and the f of the nano‐pillars is calculated as [Eq.…”
Section: The Control Of Coalescence Behaviours For Catalytic Reactionmentioning
confidence: 94%
See 1 more Smart Citation
“…The use of pillared structure on the modified surface can not only tune the wettability of liquids but also significantly affect the coalescence dynamics. More recently, the effect of arrangement density ( f ) of nano‐pillared structures on the coalescence dynamics has been reported . As shown in Figure a, the nano‐pillared surface is built by the vertical VCNTs, and the f of the nano‐pillars is calculated as [Eq.…”
Section: The Control Of Coalescence Behaviours For Catalytic Reactionmentioning
confidence: 94%
“… (a) Schematic illustration of the nano‐pillared surface, d , h and D represent the interval distance, height and diameter of nanopillars, respectively, (b) coalescence behaviours of Pb droplets on the surfaces with different f , and the graph denotes the coalescence time as a function of f , (c) coalescence behaviours of Pb droplets on the surfaces with different ∇ (0.5 Å, 1 Å, 2 Å), ∇=d′′–d′, (d) coalescence behaviours of Pb droplets on the “sparse‐dense‐sparse (SDS)”, and “dense‐sparse‐dense (DSD)” substrates . Reproduced with permission from Ref.…”
Section: The Control Of Coalescence Behaviours For Catalytic Reactionmentioning
confidence: 99%
“…Given that, the coalescing behaviors of two droplets, both on the rough surfaces modified with nanopillared structures, have been studied. 24 The results suggested that with decreasing the arrangement density of the nanopillars, a wetting transition from the "Cassie model" 25 to the "Wenzel model" 26 was observed, which is unfavorable to the coalescence process. However, when the arrangement density decreases to a very small value, the coalescing process is rather supported because the restriction effect resulting from the pillared nanostructures becomes weakened.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In their work, however, only one drop is placed on the textured surface, while the other is stationary on the smooth surface, which is less influenced by the surface structure. Given that, the coalescing behaviors of two droplets, both on the rough surfaces modified with nanopillared structures, have been studied . The results suggested that with decreasing the arrangement density of the nanopillars, a wetting transition from the “Cassie model” to the “Wenzel model” was observed, which is unfavorable to the coalescence process.…”
Section: Introductionmentioning
confidence: 99%
“…1 Functional surfaces with different wetting modes have applications in many areas such as superhydrophobic, 2,3 liquid directional transport, [4][5][6] oil-water separation, [7][8][9] and anti-icing. 10,11 The periodical grooved surface is a typical object to study the effects of factors such as dimensions, surface energy, 12 and scale of the pillar array [13][14][15] on wetting modes. Several methods or models were used to study the wetting phenomenon of the periodical grooved surface, such as the molecular dynamics simulation, 16,17 the continuum model, 18,19 the string method, 20 and the Cellular Potts Model (CPM).…”
Section: Introductionmentioning
confidence: 99%